Respuesta :
We want:
S(s) + O2(g) --> SO2(g)
So the following are the given:
1) S(s) + 3/2O2(g) --> SO3(g) ∆H = -395.8 kJ/mole
2) 2SO2 + O2 --> 2SO3(g) ∆H = -198.2 kJ/mole
Reverse Equation 2) and then divide by 2
SO3(g) --> SO2(s) + 1/2O2(g) ∆H = +99.1 kJ/mole
Add Equation 1)
S(s) + O2(g) --> SO2(g) ∆H = -296.7 kJ/mole
S(s) + O2(g) --> SO2(g)
So the following are the given:
1) S(s) + 3/2O2(g) --> SO3(g) ∆H = -395.8 kJ/mole
2) 2SO2 + O2 --> 2SO3(g) ∆H = -198.2 kJ/mole
Reverse Equation 2) and then divide by 2
SO3(g) --> SO2(s) + 1/2O2(g) ∆H = +99.1 kJ/mole
Add Equation 1)
S(s) + O2(g) --> SO2(g) ∆H = -296.7 kJ/mole